Lethality and antioxidant screening of some fractions from the dichloromethane extract of the leaves of "Baluno", Mangifera caesia - Lavilla, Charlie A. Jr.; Constantino, Juvey Mae M. (2015)
Decoction, crude ethanol, hexane extracts and some bioactive fractions from dichloromethane extract were obtained from the air-dried leaves of Mangifera caesia collected from Balo-i, Lanao del Norte. The fractions obtained through extraction with ethanol, sequential partitioning with water-hexane and dichloromethane followed by fractionation using gravity column chromatography with gradient mixture of ethyl acetate, hexane, and methanol. The cytotoxicity test of the extracts revealed that the dichloromethane extract (fraction MCD) is the most bioactive against brine shrimp Artemia salina since it requires the lowest dose to kill 50% of the tested organism. The decoction extract of M. caesia exhibited greater antioxidant potential with total ascorbic acid equivalents of 109.67 ug/ml at 500 ppm. A sub-fraction from MCD was shown to have higher potential for the presence of biologically active compounds as it showed the highest antioxidant and cytotoxic activities
Keywords: Plant extracts; Antioxidants; Toxicology